(untitled) - Mohler, James L. (Albany, New York, 2001)
This book offers information on how Flash interacts with web-based programs, complete coverage of the creation of interactive elements such as buttons, interfaces, ad banners, and animations, basic troubleshooting techniques for complex Flash site implementation, coverage of integration of sound into web presentations using Flash.
Keywords: Computer animation,Computer graphics,Flash ( computer file ),Web site; Design